Low-Intensity Extracorporeal Shock Wave as a Novel Treatment for Erectile Dysfunction - Michael M. Pan MD (American Journal of Men's Health, 2016)
The paradigm of erectile dysfunction (ED) treatment was fundamentally altered following the introduction of oral phosphodiesterase type 5 inhibitors. Unfortunately, a significant number of men exhibit a suboptimal response and require additional management strategies. One of the novel, minimally invasive strategies being developed is low-intensity extracorporeal shock wave therapy. Used in the hope of delaying placement of an inflatable penile prosthesis, the final phase of ED treatment, low-intensity extracorporeal shock wave therapy is a unique application of an established technology that may hopefully one day expand the medical options for patients with ED. This commentary will highlight the physiology underlying this technique and summarize the most recent studies.